ANALYSIS OF TRANEXAMIC ACID USAGE IN ADULT SPINAL DEFORMITY PATIENTS WITH RELATIVE CONTRAINDICATIONS IN PAKISTAN - JAVED, MA; UJJAN, BU; AMJAD, MH; ANWER , A; KHAN, NA; FAIZUDDIN, .; KHAN, N; HAQ, MIU (Biological and Clinical Sciences Research Journal, 2024)
Patients who require complex spinal surgery require a huge amount of blood transfusion perioperatively. The anemia, the formation of hematoma, and increased coagulation properties, which are consequences of massive blood loss itself can negatively affect the postoperative clinical results.Objectives: The main objective of the study is to find the tranexamic acid usage in adult spinal deformity patients with relative contraindications in Pakistan. Methodology of the study: This prospective observational study was conducted at Pakistan institute of medical sciences from 2016-2020. Data were collected from 185 patients of spine deformity.Data were collected through a combination of medical record reviews and direct patient interviews. Demographic details, including age, gender, weight, and height, were recorded for each of the 185 patients. Comprehensive medical histories were obtained to identify comorbid conditions and relative contraindications for tranexamic acid (TXA) use, such as a history of thromboembolic events, renal impairment, and concurrent anticoagulant therapy. Results: Data were collected from 185 patients according to criteria of the study. Mean age of the patients were 58.4 ± 12.3 years. Out of 185, there were 112 (60.5%) females and 73 (39.5%) male patients. Mean BMI was 28.1 ± 5.4 kg/m2. 49.7% were also suffering from hypertension, 24.3% from DM and 20% from osteoporosis.The regression coefficient (β) for total blood loss was -250 mL, with a 95% confidence interval (CI) of [-300, -200], and a p-value of < 0.001. Similarly, the regression coefficient for the number of blood transfusions was -1.2 units, with a 95% confidence interval of [-1.5, -0.9], and a p-value of < 0.001.Conclusion: Tranexamic acid effectively reduces blood loss and transfusion requirements in adult spinal deformity surgeries, even among patients with relative contraindications. The associated complication rates are manageable with careful patient selection and monitoring.